Influence analysis of metal foreign objects on the wireless power transmission system - Li, Jiacheng; Huang, Yijie (Frontiers in Electronics, 2022)
The wireless power transmission (WPT) system through magnetic field coupling for energy transmission may have foreign objects in the transmission channel in the practical application process, which brings hidden dangers to the WPT system. In this paper, a WPT system without and with foreign objects is constructed. The influence of foreign objects on self-inductance and mutual-inductance of coupling coil is studied from the aspects of foreign objects height, radius, transmission distance and coil turns. Then, by constructing the circuit topology of series structure, the influence of foreign objects on the transmission efficiency and the phase difference between voltage and current of the system is studied, and finally the influence law of metal foreign objects on the performance WPT system is summarized.